Correlation Between Quadriceps, Hamstring, Tibialis Anterior, and Gastrocnemius Muscle Activation, With Knee Flexion Angle In Basketball Athlete While Performing Double-Leg Landing Task - Utami, Ditaruni Asrina (Surabaya Physical Medicine and Rehabilitation Journal, 2020)
ABSTRACTBackground: Anterior cruciate ligament (ACL) injury cause great disability for athlete. Recent focus of ACL injury management is on prevention by identifying the risk factors. Most of basketball injury mechanism is non-contact, related to landing process with small knee flexion angle. Muscle activation and its ratio, which control movement pattern in sagittal plane, are said to play a role in dynamic movement such as landing.Aims: The purpose of this study is to analyze the correlation between muscles activation and their activation ratio of quadriceps, hamstring, tibialis anterior and gastrocnemius with knee flexion angle of basketball athlete while performing double-leg landing task.Material and methods: This study was an observational analytic, cross sectional study. Study subjects was basketball athletes age 16 – 25 years in Surabaya. Measurements of knee flexion angle done with digital measurements of reflective marker, and muscle activation was measured with sEMG while performing double-leg landing task.Result: There was no significant correlation between maximum knee flexion angle and muscle activation of quadriceps (p=0,562), hamstring (p=0,918), tibialis anterior (p=0,394) and gastrocnemius (p=0,419). There was also no significant correlation between maximum knee flexion angle and the muscle activation ratio of quadriceps-hamstring (p=0,347), quadriceps-tibialis (p=0,139), quadriceps-gastrocnemius (p=0,626), hamstring-tibialis anterior (p=0,365), hamstring-gastrocnemius (p=0,867), and tibialis anterior-gastrocnemius (p=0,109).Conclusions: There was no correlation between muscle activation and muscle activation ratio of quadriceps, hamstring, tibialis anterior and gastrocnemius with maximum knee flexion angle in basketball athlete while performing double-leg landing task.